Conflict, politics and proselytism Methodist missionaries in colonial and postcolonial Upper Burma, 1887-1966 - Leigh, Michael D. (Manchester University Press, 2011)
An exploration of Methodist missionaries working in Upper Burma between 1887 and 1966
Online Publication Date: 01 Feb 2017
Keywords: Geschichte 1887-1966; Asian history / bicssc; HISTORY / Asia / Southeast Asia / bisach; Asian history / Colonialism & imperialism / thema; Methodist Church / Missions / Burma / History / 19th century; Methodist Church / Missions / Burma / History / 20th century; Methodismus; Mission; Burma / Church history / 19th century; Burma / Church history / 20th century; Birma